The Prognostic Significance of Compliance with Postoperative Adjuvant Chemotherapy in Patients with Stage III Gastric Cancer: an Observational Study - Jang, Sung Ho; Jung, Young Jae; Kim, Min Gyu; Kwon, Sung Joon (Journal of gastric cancer, 2018)
Postoperative adjuvant chemotherapy is usually prescribed to improve the survival of patients with advanced gastric cancer who undergo curative surgery. This study was designed to determine the impact that the degree of compliance with chemotherapy has on the prognosis of patients with gastric cancer. Among 252 patients with stage III gastric cancer who underwent curative surgery between July 2004 and December 2014, 85 patients were postoperatively treated with S-1, the oral fluoropyrimidine derivative, 23 received no chemotherapy, and 144 received other regimens. Overall survival was compared between the complete compliance group (who received 8 cycles of S-1 chemotherapy, n=44) and the incomplete compliance group (who received less than 8 cycles of S-1 chemotherapy, n=41). Factors that influenced patient compliance with chemotherapy were also analyzed. The overall 5-year survival rate was significantly different between the complete chemotherapy and incomplete chemotherapy groups (80.0% vs. 42.7%, P<0.001). Based on univariate and multivariate survival analyses of patients who received S-1 chemotherapy, the independent prognostic factors were tumor, node, and metastasis (TNM) stage (IIIa vs. IIIb vs. IIIc) and compliance with chemotherapy. TNM stage and age are significant factors that influence compliance with chemotherapy. TNM stage and compliance with chemotherapy are independent prognostic factors in patients with stage III gastric cancer who received postoperative chemotherapy. TNM stage and age are significant factors that influence patient compliance with chemotherapy.